Human Parechovirus Encephalitis in a Neonate: Neuroimaging Findings - Jaya Selin Praveena Joseph; Pabbisetty Sushma; Ashok Ranjan; Senthil Kumar Aiyappan (Journal of Clinical and Diagnostic Research)
A seven-day-old female baby born of second-degree consanguineous marriage presented to the Casualty Department with a history of feeding difficulty, irritability, and seizures for one day. There were abnormal movements of the upper and lower limbs lasting less than five minutes, with 4-5 episodes in a day suggestive of bilateral multifocal chronic seizures. The baby was conscious on arrival and was admitted to the Neonatal Intensive Care Unit (NICU). The baby was delivered by lower segment caesarean section with a normal Appearance, Pulse, Grimace, Activity, and Respiration (APGAR) score of 8 and was discharged on day 3. There was no history of fever. On examination, the baby was dull and lethargic with normal vital parameters. The blood investigations were sent which included serum electrolytes, calcium, magnesium, glucose, ammonia, lactates, anion gap, pH, and ketone profile which were within normal limits. Because of the seizure and feeding difficulty, an inborn error of metabolism was suspected and the baby was subjected to Magnetic Resonance Imaging (MRI) of the brain. MRI of the brain showed no signal abnormalities in T2/Fluid Attenuated Inversion Recovery (FLAIR) images [Table/Fig-1a,b] with restricted diffusion in the subcortical, periventricular white matter of bilateral fronto-parieto-temporal lobes, external capsule, bilateral thalami, and corpus callosum [Table/Fig-2a-d]. Basal ganglia, brainstem, cerebellum, and occipital white matter were spared. Magnetic Resonance Spectroscopy (MRS) over basal ganglia was normal (Table/Fig 3). This imaging features with selective diffusion restriction involving subcortical, periventricular white matter of bilateral fronto-parieto-temporal lobes, external capsule, bilateral thalami, and corpus callosum were characteristic of Human Parechovirus (HPeV) encephalitis. On further workup for inborn errors of metabolism, Tandem Mass Spectrometry (TMS) 55 screening was normal. The baby was started on a loading dose of intravenous (IV) phenobarbitone, followed by an IV Levipil maintenance dose. On day 4 of admission, IV Levipil was changed to oral Levipil. On day 7 of admission, oral Levipil was stopped. The baby had no further seizures. Paediatric neurology opinion was obtained and an electroencephalogram (EEG) was taken on day 8 of admission, which turned out to be normal. Cerebrospinal Fluid (CSF) examination confirmed the finding of HPeV encephalitis. The baby improved symptomatically over the next few days with conservative management.